INTEGRASI ACTIVITY-BASED COSTING PADA KONSEP BISNIS LEAN UNTUK MENINGKATKAN KEUNGGULAN KOMPETITIF - Supriadi, Iman (STIE Mahardhika, 2020)
The tight competition in the industry requires companies to always make improvements in the quality of the products made to maintain a position in the competition. With the introduction of an increasingly contemporary management system, managerial decision makers tend to apply some performance management tools, one of which is Lean's business concept. This concept is characterized by the effort to eliminate waste in production, increase the value of more in one product and give value to the customer that is implemented by constantly (continuously Improvement) either from production or from all business processes in the company. In order to successfully respond to the request, the company's manager also needs an appropriate information base. One of the possible information bases is the cost assignment based on the activity. This type of research is a descriptive quality. This study discusses how the implementation and appropriateness of activity-based cost assignment for lean business concept.